Universal Immunization Programme : In Sarojininagar Block Of Lucknow District - Nirupam S; Chandra R; Srivastava V.K (Wolters Kluwer Medknow Publications, 1991)
The immunization status of infants and pregnant mothers in the community development block of Sarojini Nagar, having a population 1.6 lacs, was assessed for the year 1985-86 (pre UIP year) and again in 1987-88(post UIP year) using 30 cluster random sampling technique as proposed by WHO to study the impact of U.I.P. A significant increase in vaccine and dose-wise coverage was observed, this being 35.7%, 25.2% and 15.5% for DPT I, II & III in pre U.I.P year as compared to 69.5%, 57.1% &44.8% respectively for the post U.I.P year. Similar differences have been observed for OPV, BCG &Measles. A significant decrease in drop out rates has been observed. The percentage of fully vaccinated children although much higher (17.2% as against 1.9% in pre U.I.P. year) was still quite low in relation to the envisaged target. However, only 26.6% infants were un-immunized in 1987-88 as compared to 57.6% in 1985-86. T etvac coverage of pregnant mothers has shown a modest increase from 44.3% to 54.8%. Not many changes were observed in main reasons for non-immunization.